Children With PANS May Manifest POTS - Chan, Avis; Gao, Jaynelle; Houston, Madison; Willett, Theresa; Farhadian, Bahare; Silverman, Melissa; Tran, Paula; Jaradeh, Safwan; Thienemann, Margo; Frankovich, Jennifer (Frontiers in Neurology, 2022)
ABSTRACT Objectives: Pediatric acute-onset neuropsychiatric syndrome (PANS) is characterized by an abrupt-onset of severe psychiatric symptoms including OCD, anxiety, cognitive difficulties, and sleep issues which is thought to be a post-infection brain inflammatory disorder. We observed postural orthostatic tachycardia syndrome (POTS) which resolved with immunomodulation in a patient with Pediatric acute-onset neuropsychiatric syndrome (PANS). Here, we aim to present a case of POTS and to examine the prevalence of (POTS) in our PANS cohort and compare the clinical characteristics of patients with and without POTS. Study design: We conducted this cohort study of patients meeting PANS criteria who had at least three clinic visits during the study period. We included data from prospectively collected questionnaires and medical record review. We present a case followed by statistical comparisons within our cohort and a Kaplan-Meier analysis to determine the time-dependent risk of a POTS diagnosis. Results: Our study included 204 patients: mean age of PANS onset was 8.6 years, male sex (60%), non-Hispanic White (78%). Evidence of POTS was observed in 19/204 patients (9%) with 5/19 having persistent POTS defined as persistent abnormal orthostatic vitals, persistent POTS symptoms, and/or continued need for pharmacotherapy for POTS symptoms for at least six months). In this PANS cohort, patients with POTS were more likely to have comorbid joint hypermobility (63% vs 37%, p=0.04), chronic fatigue (42% vs 18%, p=0.03), and a family history of chronic fatigue, POTS, palpitations and syncope. An unadjusted logistic regression model showed that a PANS flare (abrupt neuropsychiatric deterioration) was significantly associated with an exacerbation of POTS symptoms (OR 3.3, 95% CI 1.4-7.6, p<0.01). Conclusions: Our study describes a high prevalence of POTS in patients with PANS (compared to the general population) and supports an association between POTS presentation and PANS flare within our cohort.